The Effect Of Capital Adequacy Ratio On Return On Assets With Problem Credit Ratio Moderation - Deni Sunaryo (Yayasan Ilomata, 2020)
The study aims to determine the effect of Capital Adequacy Ratio on Return On Asset with the moderatiom of Non Performing Loan sub sector of national foreign exchange private banks listed on the indonesian stock exchange (IDX) in 2014-2018 with a population of 22 banks. The analysis technique used are simple Linear Regression and Moderated Regression Analysis (MRA). The result showed that the Capital Adequacy Ratio has a positive and significant effect on Return On Asset. While the Capital Adequacy Ratio of Non Performing Loan is not able to moderate the Capital Adequacy Ratio with Return On Asset.